INHIBITION OF THE NKG2D ACTIVATING RECEPTOR EXPRESSION ON CYTOTOXIC LYMPHOCYTES BY RECOMBINANT MICA PROTEIN - E. V. Abakushina (SPb RAACI, 2017)
Genome instability of transformed cells, being the most common factor of malignancy, may result into production of abnormal proteins in these cells. Normally, the newly formed proteins are recognized by immune system, thus causing elimination of the transformed cells. Nevertheless, the phenotypic instability promotes formation of specific transformed cells which suppress effector immune reactions and/or are unrecognizable by cytotoxic lymphocytes. NKG2D is one of the most important activating receptors expressed by NK cells. It serves as a major recognition receptor for detection and elimination of tumor and infected cells. The ligands for NKG2D include surface or circulating non-canonical MICA/B molecules from class I major histocompatibility complex (MHC class I chain–related proteins A and B). MICA and MICB are expressed scarcely, if at all, by the most normal cells, being, however, upregulated in cancer cells and virus-infected cells.NKG2D receptor-ligand interaction is important for regulation of anti-tumor immune reactions. The soluble form of MICA accumulated in blood due to proteolytic shedding from tumor cell membranes is able to inhibit the NKG2D mediated anti-tumor cytotoxicyty and, therefore, promote the immune escape. The aim of our study was to estimate blocking effects of soluble recombinant human MICA protein (rhsMICA) upon NKG2D receptor of NK cells.Mononuclear cells were isolated from peripheral blood, followed by incubation with of rhsMICA at different concentrations (0, 1, 5, or 10 µg/ml), staining with anti-CD314 (NKG2D) mAbs on the CD3- CD56+NK cells, and flow cytometry analysis. A similar treatment protocol was applied for IL2- and IL15-activated mononuclear cells isolated from the melanoma patients.It has been shown that brief incubation of lymphocytes with rhsMICA caused a significantly reduced expression of NKG2D receptor on the surface of cytotoxic lymphocytes, both from healthy donors and melanoma patients. These changes depended on the MICA dose. Meanwhile, the cytokine-activated lymphocytes seem to become more resistant to inhibiting effects of rhsMICA, and, thus, do not cause any significant reduction of NKG2D expression on the activated NK cells. This fact may be a pre-requisite for usage of activated NK-cells for adoptive immunotherapy of cancer patients with MICA-positive malignancies.